Coping strategies and cancer incidence and mortality: The Japan Public Health Center-based prospective study. (February 2016) - Svensson, Thomas; Inoue, Manami; Sawada, Norie; Charvat, Hadrien; Iwasaki, Motoki; Sasazuki, Shizuka; Shimazu, Taichi; Yamaji, Taiki; Kawamura, Noriyuki; Shibuya, Kenji; Mimura, Masaru; Tsugane, Shoichiro; et al.
Highlights: Coping strategies used to deal with everyday problems may impact cancer outcomes. Coping strategies are associated with cancer screening and early detection of cancer. Approach-oriented coping strategies are inversely associated with cancer mortality. Abstract: Background: Psychological stress is a modifiable risk factor for health outcomes and can be managed through coping mechanisms. Biological and behavioral hypotheses have been proposed to explain the association between stress coping strategies and cancer outcomes. Methods: The Japan Public Health Center-based study asked questions on coping behaviors in its 10-year follow-up survey. 55, 130 subjects aged 50–79 without a history of cancer diagnosis and who provided complete answers on coping were included in analyses on cancer incidence and mortality. Hazard Ratios (HR) according to coping style were determined using Cox regression models adjusted for known confounders for cancer. Results: Mean follow-up time was 9.5 years for cancer incidence and 9.8 years for cancer mortality. The utilization of the approach-oriented coping strategy (HR = 0.85, 95% CI: 0.72–0.99) and a behavior of positive reappraisal (HR = 0.84, 95% CI: 0.72–0.97) was associated with a reduced risk of cancer mortality. The approach-oriented coping strategy was further associated with localized cancer incidence (HR = 1.13, 95% CI: 1.01–1.27) and screening-detected cancers (HR = 1.35, 95% CI: 1.15–1.58). The avoidance oriented coping strategy was inversely associated with cancer incidence (HR = 0.69, 95% CI: 0.50–0.94) only after excluding events occurring in the first three years of follow-up. Conclusion: The results of this study may favor the behavioral hypothesis to explain associations between premorbid coping styles and cancer outcomes.